Design and Development of a Website-Based Sales Information System at Roujee Bag Studio - Benedicta Nathania Nugroho; Ridwan Sanjaya; Albertus Dwiyoga Widiantoro (Journal of Business and Technology, 2026)
Sales Information System "Roujee Bag Studio" is an application designed to facilitate the management and monitoring of the sales process at the Roujee Bag Studio company. This application aims to improve operational efficiency, increase the accuracy of information, and strengthen control over the entire value of purchases and sales. The method used in system development is the waterfall method and the black box testing method and interviews. The results of application development show that continuity between data and integrated systems can facilitate company performance. And the existence of a strong authentication system ensures that only authorized parties can access sensitive information. with the implementation of this Sales Information System Roujee Bag Studio is expected to improve operational efficiency and more precise and accurate decision making.Keywords— sales information system, roujee bag studio, operational efficiency, data security, reporting module.